Welfare and efficiency : their interactions in Western Europe and implications for international economic relation - Geiger, Theodore; Geiger, Frances M.; NPA Committee on Changing International Realities (Washington : National Planning Association, Committee on Changing International Realities, 1978)
This study deals with one such set of new developments abroad: the effects on economic efficiency of the growth of national welfare systems in a number of West European countries and the consequences for the international competitiveness of their economies.
Includes bibliographical references and index.
ne 21/06/2018
Loans
Keywords: Public welfare; Industrial productivity; International economic relations